Effect of fenugreek seed supplementation on lactation performance of Surti buffaloes - CHOUBEY, M; PATEL, V R; RAVAL, A P; SINGH, R R (The Indian Journal of Animal Sciences, 2018)
The present experiment was aimed to evaluate the effect of fenugreek seed (FS) supplementation on lactation performance of buffaloes. Eighteen lactating Surti buffaloes were divided into 3 homogenous groups and offered with basal diet along with supplementation of overnight soaked fenugreek seed @ 0 (CON), 1.5 (FEN-1.5) and 3.0% (FEN–3.0) of total diet for 10 weeks. The daily milk yield from animals was recorded. At the end of experiment, milk samples were subjected for their constituent analysis followed by sensory evaluation. Cost of milk production was also worked out. Supplementation of FS resulted into an improvement in milk production, which was more evident at lower dose (FEN-1.5). The constituent composition of milk did not exhibit any alterations among different dietary groups. However, sensory attributes like flavour and palatability of milk showed an encouraging trend in supplemented groups. Cost of milk production was comparable across the groups. The present finding concluded that supplementation of fenugreek seeds (1.5%) in the ration of Surti buffaloes improved the milk yield with favourable impact on its sensory qualities.